Sass and compass for designers : produce and maintain cross-browser CSS files easier than ever before with the Sass CSS preprocessor and its companion authoring framework, Compass /: produce and maintain cross-browser CSS files easier than ever before with the Sass CSS preprocessor and its companion authoring framework, Compass. (©2013) - Unknown
No abstract available